5(6+2w)-6(3+5w)=8

Simple and best practice solution for 5(6+2w)-6(3+5w)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6+2w)-6(3+5w)=8 equation:


Simplifying
5(6 + 2w) + -6(3 + 5w) = 8
(6 * 5 + 2w * 5) + -6(3 + 5w) = 8
(30 + 10w) + -6(3 + 5w) = 8
30 + 10w + (3 * -6 + 5w * -6) = 8
30 + 10w + (-18 + -30w) = 8

Reorder the terms:
30 + -18 + 10w + -30w = 8

Combine like terms: 30 + -18 = 12
12 + 10w + -30w = 8

Combine like terms: 10w + -30w = -20w
12 + -20w = 8

Solving
12 + -20w = 8

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -20w = 8 + -12

Combine like terms: 12 + -12 = 0
0 + -20w = 8 + -12
-20w = 8 + -12

Combine like terms: 8 + -12 = -4
-20w = -4

Divide each side by '-20'.
w = 0.2

Simplifying
w = 0.2

See similar equations:

| 4+1.50p=14.50 | | 34+(-41)= | | f(x)=4x-1/4 | | 10(9a+6)=3(8a-2) | | 7a-(2a+5)=0 | | (3x+1)-(4x-2)=0 | | -32+(-27)= | | -17.55=9.4k+2.3k | | 2z-4-a=4 | | a-12=7a | | -10=7+1z | | 2*x^2-3*x-9=0 | | 7m+4-9m=-2(m-2) | | 6x+1=4x+47 | | 7(3q-10)=11(3q-2) | | R^2=^100/3,14 | | 17v+2v+2v-18v-2v=20 | | 4s+34=130 | | 3x-4.5x+9=12-2x | | 7/3x=5/6x-1/4 | | 4x-30=8y-20 | | -x^3-2x^2+x+2=0 | | 11x-9=14x-27 | | 60n=1500 | | X+y+5=15 | | 11q-8q-2q=5 | | R^2=100/3,14 | | 4x-3=-3+2x | | Y-2/3=13 | | dy/dx=cscx-ycotx | | 4x^2-4x+1.5=0 | | 12y-8=28y+4 |

Equations solver categories